Efektifitas Kepadatan Kandang dan Periode Pemberian Ransum yang Berbeda terhadap Performa Produksi Ayam Jawa Super Fase Finisher: The Effect of Cage Density and Feeding Period on Production Performance of Super Native Chickens Finisher Phase - Rahmawati, Nurina; Rohmad, Rohmad; Afrizal, Muhammad Deris (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2023)
The study aims to determine the production performance of super native chickens reared with cage densities of 8 birds/m2, 10 birds/m2, 12 birds/m2, and 14 birds/m2 with a feeding period of 2 and 3 times a day. The material used in this study was super-native chickens, with a total of 246 birds aged 35 days. The research method is an experimentation method with a RAL (completely randomized design) factorial pattern with 4 treatments and 3 replicates. Parameters observed were feed consumption, body weight gain, FCR, feed efficiency, and final body weight. Data were processed with ANOVA. If there is a significant difference, it will be tested with the DMRT (Duncan Multiple Range Test). The results showed that cage density and period of feeding had no significant effect (P > 0.05) on feed consumption, body weight gain, feed conversion, feed efficiency, or final body weight of super native chickens. Feed consumption has an average value of 1437.7–1511 gr/bird/day. Average body weight gain was 469–511.7 gr/bird/day, feed conversion was 2.8–3.2, feed efficiency was 31.5–44%, and the final body weight of super native chickens was 887.7–916 g/bird. The conclusion of this study is that different cage density and feeding period of super native chickens have no significant effect on their performance.